Analisis Penerapan Sistem Informasi Akuntansi Persediaan Dalam Menunjang Proses Produksi Pada Perusahaan Manufaktur Pt. Pan Pacific Jakarta Cabang Semarang - Batista Sufa Kefi; Bagus Kusuma Ardi (Universitas Katolik Widya Karya Malang, 2024)
The purpose of this research is to determine the application of the inventory accounting information system in supporting the production process at the manufacturing company PT. Pan Pacific Jakarta Semarang Branch and problems in its implementation. The research location is at PT. Pan Pacific Jakarta Semarang Branch. Analysis tools use data reduction, presenting data, and verifying conclusions. The results of the research obtained information namely PT. PAN Pacific Jakarta Semarang Branch has successfully implemented control of incoming goods through recording using a system, enabling evaluation of goods inventory. Using the Provider Inventory System with output in Excel format makes it easier to present and document data in the form of soft files and hard files. Before data is entered, incoming and outgoing goods are recorded as an initial report. The FIFO system assessment runs smoothly, as evidenced by the storage of incoming and outgoing goods data, as well as reports reflecting transaction results. Even though PT. PAN Pacific Jakarta Semarang Branch has carried out the inventory function in accordance with accounting theory, the documentation and procedures used are not fully appropriate. The use of only delivery letters as documents and the incompatibility of procedures with accounting theory indicate room for improvement in the implementation of inventory accounting information systems.